Using a Virtual Avatar Teaching Simulation and an Evidence-Based Teacher Observation Tool: A Synergistic Combination for Teacher Preparation - Craig Berg; Lisa Dieker; Raymond Scolavino (MDPI AG, 2023)
The authors describe the combination of a mixed-reality simulation program and a teacher observation software tool to gather and analyze both comments and data in a teacher preparation program. Current research on this simulation experience for teachers to practice their craft, called TLE TeachLivE, is presented, along with the general and specific uses of this mixed-reality simulator. The authors also describe a recently developed teacher observation web-based app called SeeMeTeach that provides a platform for evidence-based teacher observations both within the simulator and in real classroom settings. The authors provide a description of how the pair of tools work in concert to identify strengths and weaknesses of teacher-student discourse, student engagement in lessons, and classroom management. The synergetic use of these tools provides a low-risk opportunity to practice teaching while maximizing data gathering for optimizing feedback and coaching based on evidence. In merging TLE TeachLive and SeeMeTeach, our work examined the following research questions using a mixed-methods research design: (1) How can the teacher observation tool aid teacher educators in identifying and collecting data during a teacher observation regarding key and discrete factors in teacher-student interactions and student engagement when attempting to improve teaching effectiveness? And (2) Does the TLE TeachLivE simulation produce a realism that offers potential for a wide enough variation in the display of teaching skills so that teaching fingerprints emerge?